Volleyball selection process: How do coaches select? - Ximenes, M. D.; Rodrigues, A. J. A.; Silva, J. J.; Prudente, J. F. P. N. (Journal of Human Sport & Exercise, 2019)
When it comes to children's sport, it is important to select these athletes in competitions, so that everyone has the opportunity to compete according to their level of development and abilities. The objective of this study was to analyse the selection process used by the coaches. The sample used was 30 volleyball coaches (21 men and 9 women), aged between 21 and 62 years (39.23 ± 10.57). In order to collect information on the selection criteria used, the study was adapted from Cardoso, (2007). The study project was approved by the scientific committee of the Department of Physical Education and Sport and ethics committee of the State University of Amazonas. The Kolmogorov-Smirnov test was used to analyse the data and the mean and standard deviation statistics were used. The Kolmogorov-Smirnov test was used and the Chi-square test for qualitative variables and Spearman correlations were used in quantitative variables. T-Student was used to determine differences between groups, the Anova of repeated measures to analyse differences in the relevance attributed by the coaches to the criteria between different levels of training. The results showed relevant data such as the predominance of observation of physical education classes in children and youngsters (76.7% and 63.3%, respectively) and the application of tests in the levels of initiates and juveniles (40% and 50% % respectively). There were no divergences between the selection methods considering the characteristics of the trainer (p> 0.05).